Diversity and population structure of African fan palm (Borassus aethiopum Mart.) in Benin (West Africa) - (:unkn) unknown (My University, 2021)
The African fan palm Borassus aethiopum Mart. is widely distributed in savanna ecosystems throughout of the continent. It is an important non-timber forest product with multiple usages of significant socio-economic importance for local populations. As such, it is under strong anthropogenic pressures that have the potential to affect negatively the genetic diversity of the species. However, in spite of its role for fighting both desertification and poverty, the African fan palm remains under-studied, which hampers its sustainable development as a resource. In the present study, we analyze the genetic diversity and population structure of B. aethiopum sampled in different locations across Benin, West Africa. In order to achieve this, we have generated a partial, low-cover genomic sequencing of this species, using a high-throughput sequencing technology, and used it to identify microsatellite loci in the fan palm genome. Among these potential target loci, 11 were found to yield polymorphic amplifications between our test samples and were subsequently used in our analyses. Our results highlight the overall low genetic diversity of Borassus aethiopum populations in Benin, with number of effective alleles ranging from one point forty-four to two point zero sixty-nine per locus, and expected heterozygosity (He) ranging from zero point two hundred and sisty-three to zero point four hundred and fifty-one depending on the population. Moreover, our Bayesian analysis shows that Beninese fan palm populations are mostly structured according to geographic distances, with two population cluster including samples from the Southern and Central geo-climatic regions vs. samples from the Northern region, respectively. The present work constitutes a first step towards larger-scale genetic studies dedicated to B. aethiopum and, beyond that, provides new molecular data to the palm community.
Keywords: African Research